Evaluation of high yielding accessions of small cardamom (Elettaria cardamomum Maton) for suitability in the high ranges of Idukki District - Josephrajkumar, M Murugan, S Backiyarani, P Sainamole Kurian, A (Journal of Spices and Aromatic Crops, 2002)
Ten high yielding small cardamom accessions were collected from RRS, Mudigere; ICRI, Saklespur and CRS, Pampadumpara and evaluated for their suitability in Idukki District, Kerala. M-1 and PV -1 were found to be high yielding varieties since both of them recorded the highest yield consistently for four consecutive years. M-l was relatively tolerant to thrips infestation. The biometrical traits such as plant height, tiller number, panicle number, panicle length and seed number showed high positive correlation with yield. These characters are likely to be the ideal selection criteria in small cardamom.